Disrupted‐in‐schizophrenia 1 functional polymorphisms and D2/D3 receptor availability: A [11C]‐(+)‐PHNO imaging study. (5th July 2019) - Dahoun, Tarik; Nour, Matthew M.; Adams, Rick A.; Trossbach, Svenja; Lee, Sang H.; Patel, Hamel; Curtis, Charles; Korth, Carsten; Howes, Oliver D.
Abstract: The disrupted‐in‐schizophrenia 1 (DISC1) protein has been implicated in a range of biological mechanisms underlying chronic mental disorders such as schizophrenia. Schizophrenia is associated with abnormal striatal dopamine signalling, and all antipsychotic drugs block striatal dopamine 2/3 receptors (D2/3 Rs). Importantly, the DISC1 protein directly interacts and forms a protein complex with the dopamine D2 receptor (D2 R) that inhibits agonist‐induced D2 R internalisation. Moreover, animal studies have found large striatal increases in the proportion of D2 R receptors in a high affinity state (D2 high R) in DISC1 rodent models. Here, we investigated the relationship between the three most common polymorphisms altering the amino‐acid sequence of the DISC1 protein (Ser704Cys (rs821616), Leu607Phe (rs6675281) and Arg264Gln (rs3738401)) and striatal D2/3 R availability in 41 healthy human volunteers, using [ 11 C]‐(+)‐PHNO positron emission tomography. We found no association between DISC1 polymorphisms and D2/3 R availability in the striatum and D2 R availability in the caudate and putamen. Therefore, despite a direct interaction between DISC1 and the D2 R, none of its main functional polymorphisms impact striatal D2/3 R binding potential, suggesting DISC1 variants act through other mechanisms. Abstract : No effects of the DISC1 SNPs Ser704Cys, Leu607Phe and Arg264Gln on striatal D2/3R availability.